Achieving optimum natural daylighting strategies in a design studio of UiTM Perak / Muhammad Anas Othman - Othman, Muhammad Anas (2019)
Malaysian universities are facing various environmental issues in the design studios due to the diverse activities and longer period of occupancy in this educational space. Students tend to stay in the design studios in a longer period which resulting towards inefficient use of energy, especially from the lighting aspect. Issue like gloomy or shaded areas due to inefficient natural lighting penetration has influenced the studio’s users to use excessive artificial lighting even during the day. Whilst, issue like glare and over-lighting from the sunlight has influence the studio’s users to use curtain or blinds which eventually leading to the use of artificial lighting. This may increase the electricity bill due to uncontrolled consumption of artificial lighting and produce more energy waste which can minimise the possibility of achieving greener spaces in a university. Therefore, this research aims to identify the optimum natural daylighting strategies that can be integrated in these design studios in order to improve the passive lighting penetration towards achieving greener spaces in a university. By identifying significant daylighting strategies, the utilisation of artificial lighting in the design studios can be reduced. UiTM Perak branch, a university that predominantly has design-based programs, has been chosen as the case study to test on this matter. This study involves the experimental research design which covers on the quantitative approaches to achieve the aim and objectives of this research.